Perbedaan Kesadaran Kesehatan Reproduksi antara Calon Pengantin Laki-laki dan Perempuan di Kota Surakarta - Syifa Marhattya Rizky; Diffah Hanim; Anik Lestari (Nexus Kedokteran Komunitas, 2014)
Background:People who enters early adulthood phase is considered capable, both physically and mentally, to get married and having children. Before holding their marriage everyone should have basic knowledge and good attitude of reproductive health. But the stigma of gender makes most people think that the awareness of reproduction health only becomes a liability for women. This study aimed to determine whether there was difference in reproductive health awareness among grooms and brides in Surakarta. Methods:This study was analytic observational study used cross-sectional design. Total of 70 subjects consisted of 35 prospective grooms and 35 brides, were selected by purposive sampling method. It had been done in Office of Religious Affair of five sub districts in Surakarta. The data were collected by interview used a set of questionnaire and analyzed byusingIndependent Sample T- test and Two Way Anova. Results:This study showedthe mean score on the reproductive health awareness for prospective grooms were 21.37 2.82 and for the prospective brideswere 22.85 3.05. Independent Sample T-Test showed p = 0.038. Conclusions:There was a difference of reproductive health awareness between the prospective groom and bride. Reproductive health awareness of prospective bride was better than the prospective groom. Keywords:Awareness, reproductive health, prospective groom and bride